2004
DOI: 10.1073/pnas.0306712101
|View full text |Cite
|
Sign up to set email alerts
|

CO migration in native and mutant myoglobin: Atomistic simulations for the understanding of protein function

Abstract: Molecular dynamics simulations of the events after the photodissociation of CO in the myoglobin mutant L29F in which leucine is replaced by phenylalanine are reported. Using both classical and mixed quantum-classical molecular dynamics calculations, we observed the rapid motion of CO away from the distal heme pocket to other regions of the protein, in agreement with recent experimental results. The experimentally observed and calculated infrared spectra of CO after dissociation are also in good agreement. We c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

12
97
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
9
1

Relationship

5
5

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 25 publications
12
97
0
1
Order By: Relevance
“…Several simulations (23,24,26) and time-resolved x-ray crystallography studies (17,18) have shown that ligand trajectories from the distal pocket to Xe4 are the most probable route of ligand movement into the protein interior after photodissociation. For the H64L/V68F double mutant, the combination of reduced steric hindrance at the iron and partial filling of the Xe4 cavity combine to cause ϳ100% geminate recombination from the initial B state, and the observed kinetic phase can be assigned with certainty to geminate recombination from the initial docking site labeled as "B" in the structure of wild-type MbCO shown in Fig.…”
Section: Of Ref 49) (13)mentioning
confidence: 99%
“…Several simulations (23,24,26) and time-resolved x-ray crystallography studies (17,18) have shown that ligand trajectories from the distal pocket to Xe4 are the most probable route of ligand movement into the protein interior after photodissociation. For the H64L/V68F double mutant, the combination of reduced steric hindrance at the iron and partial filling of the Xe4 cavity combine to cause ϳ100% geminate recombination from the initial B state, and the observed kinetic phase can be assigned with certainty to geminate recombination from the initial docking site labeled as "B" in the structure of wild-type MbCO shown in Fig.…”
Section: Of Ref 49) (13)mentioning
confidence: 99%
“…The photosensitive Fe-ligand bond has allowed transient intermediates to be studied by flash photolysis methods ranging from spectroscopy (1, 5-7) to x-ray crystallography (9)(10)(11)(12)(13)(14)(15)(16). Since the seminal work of Case and Karplus (17), Mb has also been the target of molecular dynamics (MD) simulations (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). This combination of experimental and theoretical investigations has made Mb one of the most thoroughly studied proteins.…”
mentioning
confidence: 99%
“…In 2010, Elber (22) reviewed the most recent computational literature, which still indicates that there are multiple ligand pathways in animal myoglobins and hemoglobins and that the channel gated by the distal histidine is only a minor route for entry and exit (23)(24)(25)(26)(27)(28)(29)(30)(31).…”
mentioning
confidence: 99%